INDUSTRI FILM INDONESIA SEBAGAI BAGIAN DARI INDUSTRI KREATIF Indonesia - Chitra Lestari, S.I.Kom, M.I.Kom, Chitra Lestari, S.I.Kom, M.I.Kom (Akademi Komunikasi SAE Indonesia, 2022)
There are many public businesses in the creative industries that are mostly profitable. In this era of technological development, we must be more creative. This study aims to (1) determine the conditions and value chain of creative businesses in the backing film sector in Indonesia. (2) knowing the efforts of the government to support creative businesses in film in Indonesia. The discussion methodology used is SWOT analysis. The data used in this research is a literature study. The conclusion of this study is that the condition of the Indonesian creative film sub-sector in the last two decades has shown significant developments compared to the previous administration. Films can be described through chain operations, supporting related products and regulations. Constraints faced by companies in supporting the creative film subsector in Indonesia, in particular, include limited hype programs that support film products that are less attractive to the public, delays in company operations, foreign film technology that is increasingly popular among the Indonesian people, weak government regulations. maintaining a film trail, and the lack of film seminaries in Indonesia. Results for Film, which is more in terms of marketing, uses more sophisticated technology as used by developed countries, and the government should be more involved in backing Indonesian films